TSN Incremental Routing and Scheduling through parallel MILP computation - Gracia Rodríguez, Alex; Segarra Flor, Juan; Briz Velasco, José Luis; Torres Macías, Alitzel Galilea; Ramirez Treviño, Antonio; Blanco Alcaine, Hector (Jornada de Jóvenes Investigadores del I3A, 2025)
Time-Sensitive Networking (TSN) ensures deterministic communication using IEEE 802.1Qbv’s Time Aware Shaper (TAS). Generating Gate Control Lists (GCL) is computationally heavy for dynamic systems. We propose an incremental MILP framework for joint routing and scheduling. It finds solutions faster and achieves complete schedules where monolithic methods fail